2010
DOI: 10.1016/j.fgb.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the role of the microtubule binding protein Bim1 in Cryptococcus neoformans

Abstract: During sexual development the human fungal pathogen Cryptococcus neoformans undergoes a developmental transition from yeast-form growth to filamentous growth. This transition requires cellular restructuring to form a filamentous dikaryon. Dikaryotic growth also requires tightly controlled nuclear migration to ensure faithful replication and dissemination of genetic material to spore progeny. Although the gross morphological changes that take place during dikaryotic growth are largely known, the molecular under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Staudt et al demonstrated a conserved role of the microtubule‐associated protein Bim1 in hyphal morphology. Crosses between bim1 Δ mutants produced unusually short and curved filaments with missegregated nuclei (Staudt et al , 2010).…”
Section: Development Of Postmating Hyphaementioning
confidence: 99%
See 1 more Smart Citation
“…Staudt et al demonstrated a conserved role of the microtubule‐associated protein Bim1 in hyphal morphology. Crosses between bim1 Δ mutants produced unusually short and curved filaments with missegregated nuclei (Staudt et al , 2010).…”
Section: Development Of Postmating Hyphaementioning
confidence: 99%
“…Staudt et al demonstrated a conserved role of the microtubule‐associated protein Bim1 in hyphal morphology. Crosses between bim1 Δ mutants produced unusually short and curved filaments with missegregated nuclei (Staudt et al , 2010). Similarly, in Schizophyllum commune , nuclear migration was associated with microtubule tracks and microtubule‐associated motors (Raudaskoski, 1998).…”
Section: Development Of Postmating Hyphaementioning
confidence: 99%
“…This group showed enrichment for genes with functions relating to the cytoskeleton, particularly those components that destabilize microtubules and cytoskeletal components. Cluster 8 also includes BIM1, whose gene product is known to contribute to proper microtubule organization (Staudt et al 2010).…”
Section: Gene Expression Profiling Of C Neoformans During Sexual Devmentioning
confidence: 99%
“…Maintenance of MT structural integrity by this class of +TIP was also observed in the budding yeast Bim1 homologue of the human pathogen Cryptococcus neoformans [44]. Abnormally short and relatively unstructured MTs were observed in bim1 mutants in filaments during sexual development and during diploid filamentation, consequently changing its normal filamentous growth [44]. Similarly, MT dynamics, specifically during G1 phase of cell division, has been shown on studies of S. cerevisiae Bim1 [15].…”
Section: Discussionmentioning
confidence: 61%
“…Lack of mal3 resulted in short and often weak cytoplasmic MTs [16]. Maintenance of MT structural integrity by this class of +TIP was also observed in the budding yeast Bim1 homologue of the human pathogen Cryptococcus neoformans [44]. Abnormally short and relatively unstructured MTs were observed in bim1 mutants in filaments during sexual development and during diploid filamentation, consequently changing its normal filamentous growth [44].…”
Section: Discussionmentioning
confidence: 81%